2005
DOI: 10.1093/molbev/msj016
|View full text |Cite
|
Sign up to set email alerts
|

Evolution by Recombination and Transspecies Polymorphism in the MHC Class I Gene of Xenopus laevis

Abstract: The patterns of major histocompatibility complex (MHC) evolution involve duplications, deletions, and independent divergence of loci during episodes punctuated by natural selection. Major differences in MHC evolution among taxa have previously been attributed to variation in linkage patterns of class I and class II MHC genes. Here we characterize patterns of evolution in the MHC class Ia gene of Xenopus laevis in terms of polymorphism, recombination, and extent of transspecies polymorphism. We also compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 49 publications
8
37
0
1
Order By: Relevance
“…One possible mechanism underlying these results is the exchange of entire exons during recombination, as opposed to shorter motifs within exons. In X. laevis, at least two recombinant alleles (Xela-UAA*06 and UAA*11) have identical a1 domain sequences, but divergent a2 and a3 domains (Bos and Waldman, 2006a). Our results are consistent with this pattern, especially given that we amplified sequences from five of the six species that were identical in one domain, but differed in others.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…One possible mechanism underlying these results is the exchange of entire exons during recombination, as opposed to shorter motifs within exons. In X. laevis, at least two recombinant alleles (Xela-UAA*06 and UAA*11) have identical a1 domain sequences, but divergent a2 and a3 domains (Bos and Waldman, 2006a). Our results are consistent with this pattern, especially given that we amplified sequences from five of the six species that were identical in one domain, but differed in others.…”
Section: Discussionsupporting
confidence: 85%
“…Overall, while the number of unique MHC class I sequences within individuals in this study is striking when compared with other frogs examined to date, our results are not entirely unexpected, especially given the small percentage of frog species whose MHC genes have been characterized (Figure 1) and the diversity of ploidy levels within anurans. MHC variability is predominantly caused by the accumulation of point mutations over millions of years, with recombination, gene duplication and gene convergence generating additional allelic diversity (Parham and Ohta, 1996;Little and Parham, 1999;Bos and Waldman, 2006a). The large number of sequences recovered within individual frogs in this study may also reflect the joint effects of intraand interlocus recombination acting across several MHC class I paralogs.…”
Section: Discussionmentioning
confidence: 82%
“…Sharing of MHC alleles between species from the same genus has been found in several recently diverged taxonomic groups, such as Xenopus frogs (Bos and Waldman, 2006), Spheniscus penguins (Bollmer et al, 2007;Kikkawa et al, 2009), equids (Kamath and Getz, 2011) and primates (Doxiadis et al, 2006). The divergence between all three Tympanuchus species likely occurred within the last 0.5-2 million years, and in areas of geographic overlap, hybridisation has been observed between T. cupido and two other Tympanuchus grouse (Galla and Johnson, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…However, relatively few studies have focused on the evolution of amphibian MHC class I genes, and those few studies have involved a limited number of amphibian species, mainly Ambystoma mexicanum in the Caudata [36] and two closely related Pipidae species ( Xenopus lavies and X. (Silurana) tropicalis ) in the Anura [37-39]. These studies revealed that (1) Urodela ( Ambystoma ) have multiple MHC class I loci [36], whereas the Anura (Pipidae and Ranidae) have only one [37-41]; it is possible that the number of MHC class I loci increased after the Urodela and Anura but before the Pipidae and Ranidae diverged [40].…”
Section: Introductionmentioning
confidence: 99%